Pengaruh Copywriting Emosional terhadap Engagement di Platform Sosial Berbasis Algoritma Kurasi : Seperti Reels & FYP Tiktok - Zuhrinal M. Nawawi; Siti Nurhalimah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
This research uses a qualitative method to examine the influence of emotional copywriting on user engagement in algorithm-curated social media platforms such as Instagram Reels and TikTok’s For You Page (FYP). The increasing consumption of short-form, personalized content driven by user behavior highlights the need for more targeted communication strategies. Emotional copywriting—writing that emphasizes affective elements such as empathy, joy, fear, or nostalgia—is considered effective in creating emotional bonds between content creators and audiences, thus encouraging interactions like likes, comments, and shares. This study was conducted through content analysis of 25 viral videos with high engagement, along with in-depth interviews with five active content creators. The findings reveal that using emotionally resonant phrases aligned with users’ social values and experiences significantly boosts content performance within algorithmic systems. Emotionally charged content tends to receive broader exposure as algorithms prioritize highly interactive posts. Therefore, emotional copywriting is not only a creative strategy but also an effective tactic for optimizing content visibility in the age of social media algorithms. Keywords: , , , , , Reels, , social platforms.